2001
DOI: 10.1034/j.1600-0404.2001.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis: modulation of apoptosis susceptibility by glatiramer acetate

Abstract: Our findings indicate that therapy of multiple sclerosis with glatiramer acetate presumably involves the compensation of altered apoptosis in T-helper lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In two reports [1,13] evidence of a modulation in peripheral T-cell apoptosis during treatment with GA has been also provided. Aktas and colleagues [1] showed that T-cells apoptosis, after in vitro stimulation with GA, declined under the baseline and was equal in treated patients and controls.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In two reports [1,13] evidence of a modulation in peripheral T-cell apoptosis during treatment with GA has been also provided. Aktas and colleagues [1] showed that T-cells apoptosis, after in vitro stimulation with GA, declined under the baseline and was equal in treated patients and controls.…”
Section: Discussionmentioning
confidence: 94%
“…Aktas and colleagues [1] showed that T-cells apoptosis, after in vitro stimulation with GA, declined under the baseline and was equal in treated patients and controls. Hence the authors demonstrate a general involvement of GA in the compensation of altered apoptosis in T helper cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To study apoptosis sensitivity isolated PBMC were cultured either without any stimuli or with PHA plus IL-2 and spontaneous cell death or anti-CD95 mAbmediated cell death was measured [25][26][27][28]38]. When apoptosis sensitivity of PBMC from MS patients was compared to healthy controls a small relative resistance of MS-PBMC was found [25][26][27] or was even not detectable [28,38].Yet, such studies do not reflect that autoreactive T cells might only represent a small minority within a mixture of mononuclear cells which could exhibit a different apoptosis phenotype. Our findings clearly show that a small subpopulation such as T reg can exhibit just the opposite phenotype regarding spontaneous and inducible apoptosis in comparison to the majority of T cells mixed with.…”
Section: Discussionmentioning
confidence: 99%
“…In previous experiments, we assessed the in vitro apoptosis susceptibility of CD4+ T cells and found that untreated MS patients showed an impaired apoptosis compared with healthy individuals [22]. Interestingly, subsequent therapy of these patients with GA led to a compensation of the observed in vitro differences, indicating that GA therapy might involve the modulation of apoptosis pathways.…”
Section: Introductionmentioning
confidence: 99%